Analysis of The Presence of Pathogen Bacteria in Rectal Swab of Food Handler at The Yogyakarta Health and Calibration Laboratory: Analisis Keberadaan Bakteri Patogen pada Rectal Swab Penjamah Makanan di Balai Laboratorium Kesehatan dan Kalibrasi Yogyakarta - Ratna Kusumaningtyas; Dhiah Novalina; Irfani, Farida Noor (Universitas Muhammadiyah Sidoarjo, 2024)
Food handlers are workers who are responsible for handling food from preparation to serving. In accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 1096/MENKES/PER/VI/2011, food handlers must be checked periodically every six months by carrying out anal swabs to find out whether the food handler is free. of pathogenic bacteria and act as carriers or not. This study aims to find out whether food handlers who work at Food Management Places (TPM) in Yogyakarta act as careers or not through identifying pathogenic bacteria in rectal swab samples. The type of research used was descriptive qualitative with a cross-sectional approach by taking data at BLKK Yogyakarta from January to December 2023. The sample in this study amounted to 86 data using a purposive sampling technique based on inclusion and exclusion criteria. Data were analyzed for frequency distribution and Chi-Square and Odds Ratio statistical tests were carried out. The results of the study showed that the examination was dominated by the TPM type, namely catering class B (hospital) as many as 4 (40,0%) applicants, the early adult age group (18-40 years) as many as 73 (84,9%) and gender men were 44 (51,2%) food handlers. The results of the rectal swab examination showed positive Escherichia coli bacteria (carrier) in 33 (38,4%) food handlers and there was a significant relationship between the results of the examination for pathogenic bacteria and TPM sanitation (p-value 0,023), but there was no significant relationship between results of examination of pathogenic bacteria with age (p-value 0,531) and gender (p-value 0,695).